Skin diseases in a Nepali prison - Parajuli, N; Jonkman Veenstra, G; Jonkman, M (Journal of Chitwan Medical College, 2015)
Here we report on the pattern of dermatoses presented during a dermatological camp in Bharatpur prison. A total of 119(27.2%) inmates out of 437 inmates had dermatological problem. Most common dermatoses were skin infections (34.8%). Among the infections, fungal infections were most common (82%). In non-infectious group eczematous disorders and pigmentary disorders were common. Overcrowding in prison with three times excess could be contributing factor for the excess infections DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11968